2021
DOI: 10.3389/fcell.2021.634355
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Depleted miR-146a in ALS Cortical Astrocytes Reverts Cell Aberrancies and Prevents Paracrine Pathogenicity on Microglia and Motor Neurons

Abstract: Reactive astrocytes in Amyotrophic Lateral Sclerosis (ALS) change their molecular expression pattern and release toxic factors that contribute to neurodegeneration and microglial activation. We and others identified a dysregulated inflammatory miRNA profile in ALS patients and in mice models suggesting that they represent potential targets for therapeutic intervention. Such cellular miRNAs are known to be released into the secretome and to be carried by small extracellular vesicles (sEVs), which may be harmful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 145 publications
(231 reference statements)
4
40
0
Order By: Relevance
“…In the past years, it was demonstrated that miRNAs are not only present intracellularly, but are also detectable in substantial amounts extracellularly, including in biological fluids, being present either in exosomes or as soluble components in the vesicle-free secretome [83]. This horizontal transfer of miRNAs is part of autocrine and paracrine signaling mechanisms involved in cell-to-cell communication and in the propagation of inflammatory mediators, including miRNAs [11,84,85]. In this study, we have shown that SH-WT and SH-SWE cells overexpressing miR-124 are responsible for its enhanced expression in donor cells, when using a non-contact co-culture system, thus attesting the cell-to-cell transfer of this miRNA [64].…”
Section: Discussionmentioning
confidence: 99%
“…In the past years, it was demonstrated that miRNAs are not only present intracellularly, but are also detectable in substantial amounts extracellularly, including in biological fluids, being present either in exosomes or as soluble components in the vesicle-free secretome [83]. This horizontal transfer of miRNAs is part of autocrine and paracrine signaling mechanisms involved in cell-to-cell communication and in the propagation of inflammatory mediators, including miRNAs [11,84,85]. In this study, we have shown that SH-WT and SH-SWE cells overexpressing miR-124 are responsible for its enhanced expression in donor cells, when using a non-contact co-culture system, thus attesting the cell-to-cell transfer of this miRNA [64].…”
Section: Discussionmentioning
confidence: 99%
“…mechanisms (15,17), modulation of such mechanisms with specific miRNAbased strategies may prevent cell-to-cell paracrine dysregulation and MN degeneration (81,86).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a decreased cargo in miR-494-3p was found in C9ORF72 astrocyte-derived exosomes with harmful consequences in neurite network in ALS (89). Depleted levels of miR-146a were also recognized in exosomes from the cortical astrocytes of mSOD1 mice (15), and its cellular replenishment abrogated the astrocyte aberrant phenotype, characterized by increased S100B and Cx43 levels, together with decreased GFAP, while leading to a secretome with paracrine neuroprotective properties (81). Exosomes from both cortical and spinal mSOD1 astrocytes were deficient in miR-155, miR-21 and miR-146a (12).…”
Section: Dysregulated Autocrine/paracrine Signaling Mechanismsmentioning
confidence: 94%
See 1 more Smart Citation
“…In mouse models of ALS, SOD1 mutant astrocytes release EVs that increase microglial expression of inducible nitric oxide synthase (iNOS) and TNF-alpha. These changes are associated with microglial activation, but the ADEVs were also found to induce apoptosis of microglia [ 73 ]. It is well recognized that microglia are important activators of astrocyte responses in a range of human neurological diseases, these ADEV focused studies also indicate a reciprocal communication from astrocyte to microglia, which may have similar influence and impact on neuropathology and function.…”
Section: Adevs Facilitate Intercellular Communicationmentioning
confidence: 99%